Preliminary characteristic of bubble deck slab subjected to a vertical point load - Nor Shahirah, Mohd Zulkifli; Nor Ashikin, Muhamad Khairussaleh; Roslina, Omar (UKM Press, 2025)
The bubble deck slab system, formally recognised as the reinforced bubble deck slab, presents a distinctive structural solution contributing to the optimisation of building functionality and design especially in modern construction. Compared to traditional solid slabs, this study examines the initial properties of bubble deck slabs under vertical point loads, with particular attention to bending effects, deflection behaviour, and failure causes under controlled experimental conditions. The primary objectives of this study are to evaluate the deflection of both slab types, determine failure conditions, and examine the response to point loads applied at their edges with special focus on the stiffness characteristics of the slabs. This inventive slab, made of reinforced concrete, incorporates hollow plastic bubble balls made of high-density polyethylene (HDPE), which reduces the overall concrete volume compared to conventional reinforced concrete slabs. Under the shear point load applied at the centre of the slab, the bubble deck slabs exhibited superior elastic behaviour compared to their conventional counterparts. Consequently, the bubble deck slab in this study significantly reduces concrete usage. Despite the reduced concrete volume, the strength and performance characteristics of bubble deck slabs are maintained. A detailed examination of the applied loads explores their effects on flexural strength, bending stiffness, and load-deflection behaviour, providing a comprehensive understanding of the system’s structural performance and potential application in sustainable building design.